2011
DOI: 10.1186/1751-0759-5-13
|View full text |Cite
|
Sign up to set email alerts
|

A before and after comparison of the effects of forest walking on the sleep of a community-based sample of people with sleep complaints

Abstract: BackgroundSleep disturbance is a major health issue in Japan. This before-after study aimed to evaluate the immediate effects of forest walking in a community-based population with sleep complaints.MethodsParticipants were 71 healthy volunteers (43 men and 28 women). Two-hour forest-walking sessions were conducted on 8 different weekend days from September through December 2005. Sleep conditions were compared between the nights before and after walking in a forest by self-administered questionnaire and actigra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 31 publications
(37 reference statements)
5
55
1
4
Order By: Relevance
“…In Scandinavian nations, concepts such as friluftsliv, open-air life, are in common use as part of national culture. In Japan and Korea, there is a widespread practice known as shinrin-yoku, "forest bathing, " as a deliberate measure to improve health (Li, 2010;Shin et al, 2010;Li et al, 2011;Morita et al, 2011;Craig et al, 2016). In China, there is a longstanding historical precedent for the philosophy of tian ren he yi, harmony between people and nature-even if, as in other nations, this may not be practiced in economic development.…”
Section: Mental Health Outcomesmentioning
confidence: 99%
“…In Scandinavian nations, concepts such as friluftsliv, open-air life, are in common use as part of national culture. In Japan and Korea, there is a widespread practice known as shinrin-yoku, "forest bathing, " as a deliberate measure to improve health (Li, 2010;Shin et al, 2010;Li et al, 2011;Morita et al, 2011;Craig et al, 2016). In China, there is a longstanding historical precedent for the philosophy of tian ren he yi, harmony between people and nature-even if, as in other nations, this may not be practiced in economic development.…”
Section: Mental Health Outcomesmentioning
confidence: 99%
“…Research 39 has shown that many aerobic or resistance exercise may be a supported intervention for insomnia in a clinical practice, allowing the patient to select it according to his preference. A chinese exercise program with Tai Chi Chih 40 and a forest walking 41 improved sleep quality in insomniacs. The practice of Bikran yoga 42 during a 14day period was associated with significantly faster return to sleep after nocturnal awakenings.…”
Section: Intervention: Exercisementioning
confidence: 96%
“…Walking may contribute to better sleep quality because of the e cacy in stress reduction and physical exercise involved. 10 Nevertheless, Buckworth highlighted that gender-related relationships between sedentary and active behaviors should be considered and to promote exercise in young adult population. 4 The National Institute for Health (NIH) and Clinical Excellence suggested that physical activity should be consist for three sessions of 45-60 minutes per week for a period of at least 10-14 weeks.…”
Section: Introductionmentioning
confidence: 99%